Unraveling the Mysteries of Autoimmune Gastritis - Soykan, İrfan and Er, Ramazan Erdem and Baykara, Yigit and Kalkan, Cağdaş (Turkish Journal of Gastroenterology, 2024)
Autoimmune gastritis is an immune-mediated disease characterized by the destruction of parietal cells and atrophy of the oxyntic mucosa due to anti-parietal cell antibodies. It may lead to serious conditions including iron/vitamin B12 and micronutrient deficiencies, neurological disorders, and gastric malignancies. The exact mechanism of this disease is not exactly understood; however, dysregu lated immunological mechanisms appear to be major contributors. Patients with this disease are often asymptomatic but may present with gastrointestinal symptoms and/or iron/vitamin B12 deficiencies. Although important serological markers are available and despite advanced endoscopic techniques, the definitive diagnosis relies on histopathological examination of gastric corporal biopsy specimens. Autoimmune gastritis is closely related with increased risk of gastric neuroendocrine tumors and gastric adenocarcinoma. Patients with autoimmune gastritis do not benefit from specific treatments, thus, management is directed to restore micronutrient deficiencies and to prevent occurrence of neoplastic transformation with appropriate endoscopic surveillance. Cite this article as: Soykan İ, Er RE, Baykara Y, Kalkan C. Unraveling the mysteries of autoimmune gastritis. Turk J Gastroenterol. 2025;36(3):135-144.